Molecular pathology of microRNA-103a as a probable diagnostic and therapeutic tumor marker - Iman Akhlaghipour; Negin Taghehchian; Meysam Moghbeli (Advances in Cancer Biology - Metastasis)
Late diagnosis has a key role in therapeutic failure and tumor relapse. Therefore, assessment of the molecular tumor biology can help to introduce novel early diagnostic markers. MicroRNAs (miRNAs) have important roles in regulation of tumor cell proliferation, invasion, drug resistance, and angiogenesis. Due to the high stability of miRNAs in paraffin-embedded tissues and body fluids, they can be also used as the non-invasive markers for cancer screening and early diagnosis. According to numerous reports about the role of miR-103a in various cancers, in the present review we investigated the molecular biology of miR-103a during tumor progression. It has been reported that miR-103a has a dual function as an oncogene and tumor suppressor in various cancers. MiR-103a exerts its role in tumor progression by regulation of signaling pathways, apoptosis, cell cycle, cell metabolism, and transcription factors. This review paves the way in introducing miR-103a as a diagnostic and therapeutic marker among cancer patients following the animal studies and clinical trials.